2020
DOI: 10.2298/sjee2002187n
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Symlet filter based on ECG baseline wander removal

Abstract: In this paper, proposed a new approach of combining the hybrid soft computing technique called Adaptive Symlet Wavelet Transform (ASWT) filter. The baseline wanders (BW) noise removal from an ECG signals to minimize distortion of the S-T segment of the ECG signal specially that have high sampling frequencies. Therefore, when using Symlet Wavelet Transform (SWT) to analysis the ECG signal can cause problems to analysis, exclusively when examining the content of the ECG signal at low-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Tropical addition can replace traditional addition as a more effective filter in denoising. In 2020, Nahar 46 proposed a new method combined with hybrid soft computing technology-adaptive wavelet transform (ASWT) filtering. It can be concluded that tropical addition is the optimal scheme for noise filtering, and the filter based on tropical addition can achieve the filtering effect more efficiently and easily.…”
Section: Applicationsmentioning
confidence: 99%
“…Tropical addition can replace traditional addition as a more effective filter in denoising. In 2020, Nahar 46 proposed a new method combined with hybrid soft computing technology-adaptive wavelet transform (ASWT) filtering. It can be concluded that tropical addition is the optimal scheme for noise filtering, and the filter based on tropical addition can achieve the filtering effect more efficiently and easily.…”
Section: Applicationsmentioning
confidence: 99%